Literacy Education: Communication Literacy Model in Tudang Sipulung Culture in Patondonsalu Village at Enrekang District - Ismaya; Mahmuddin; Arifuddin Tike; I Ibrahim (SAGA: Journal of Technology and Information System, 2023)
This type of research is descriptive qualitative research conducted in the village of Patondonsalu, Enrekang Regency, focusing on the communication literacy model in the Tudang Sipulung culture. The results showed that the communication literacy model in the implementation of culture tudang sipulung in the Patondonsalu village is fine enough because it has fulfilled elements: identification topic/subject, target audience, relevant formats, types source; exploration sources, and information appropriate to the topic; organization, evaluation and compiling information according to the logical arrangement, distinguishing among facts and opinions, and uses visual tool aids for comparing and contrasting information; (who); (what is said); (communication channel); (to whom); and with what effect (element of influence/effect) or what is the effect of the communication. However, the applied communication literacy model is not yet maximum because there is not yet relevant selection and recording information, the creation information not yet well done, presentation, dissemination or display of information from results activity tudang sipulung also out yet there. Then output appraisal, based on other people input from implementation culture tudang sipulung still very low and almost no at once